Happy Earth - Class Book 1. Teacher's book - BOWLER, Bill (Oxford Oxford university press, 2012)
New edition of Happy Earth, topic based course that builds on early reading and writing, extending vocabulary and structures from the first years of english. By drawing on a wide range of factual information, it develops children's language skills and awareness of the world.
Contents, tests.
Keywords: Langue anglaise; Expression orale; Expression écrite